Current status of dental metal allergy in Japan. Issue 3 (July 2019) - Kitagawa, Masae; Murakami, Satoshi; Akashi, Yoshihiko; Oka, Hiroko; Shintani, Tomoaki; Ogawa, Ikuko; Inoue, Takashi; Kurihara, Hidemi
Abstract: Purpose: To assess the current status of patients with dental metal allergies in Japan. Methods: This study analyzed dental metal allergy in 1225 patients (1:3 male to female ratio; average age 53.0 ±16.5 years), including 300 who were scheduled to undergo dental implant surgery, between 2006 and 2016. For diagnosis of metal allergy, patch tests using metal allergens were performed. Additionally, when necessary, metal element analysis of dental alloys was performed in the mouths of some patients using an X-ray fluorescence analyzer for those who exhibited positive reactions. Results: Among 925 patients (i.e., excluding those scheduled to undergo dental implant surgery [n = 300]), nearly one-half (44.0%) exhibited a positive response to any metal element in the patch test. The positivity rates were as follows: nickel (22.5%); palladium (14.8%); and zinc (11.5%). Almost one-half (42.3%) of the patients had diseases associated with metal allergy. Among patients who exhibited a positive reaction to any metal element in the patch test, more than two-thirds (67.9%) had dental alloys containing the positive metal element(s). One-half (55.6%) of the patients who underwent treatment to remove the metal experienced improvement in symptoms. In patients who underwent patch testing as an implant preoperative examination, several (2.7%) exhibited a positive reaction to titanium. Conclusions: Dental metals, including nickel, palladium and zinc, which are indispensable to dental treatment in Japan, had high positivity rates in patch testing, and one-half of the patients improved following removal of the metal. Additionally, there were several patients with allergy to titanium.